Factors that influencing default loan repayment among micro-entrepreneurs / Siti Noor Hidayuu Kamalrulzaman, Wei-Loon Koe and Shafinar Ismail - Kamalrulzaman, Siti Noor Hidayuu; Loon Koe, Wei; Ismail, Shafinar (Universiti Teknologi MARA, Cawangan Melaka, 2017)
The expansion of Microfinance Institutions (MFIs) has experienced high growth and the implication is that increased competition could lead to a higher incidence of default. Since the borrower responsible for their own individual loan either in group lending and individual lending, intention are the best predictor as indications of a person’s readiness to perform a specific behaviour. This study will identify the factors that causes from MFIs expansion such as motivation for future loan, family business capital, and self-efficacy towards double dipping that influence default loan repayment intention. The Theory of Planned Behavior is used as the focal theory. The empirical results of this study will assist in policy development eventually affects the sustainability capacity of MFIs.